2015
DOI: 10.1039/c5bm00171d
|View full text |Cite
|
Sign up to set email alerts
|

Multi-stage, charge conversional, stimuli-responsive nanogels for therapeutic protein delivery

Abstract: A boronate ester crosslinked zwitterionic nanogel (NGCA) with ATP/pH-sensitivity has been developed with an inverse nanoprecipitation technique to achieve a two-stage charge conversion that responds to tumor extracellular conditions (pH 6.5-6.8) and an intracellular acidic environment (pH 5-6). Cationic cytochrome C (CC), a therapeutic protein, has been encapsulated into NGCA through inverse nanoprecipitation via electrostatic interactions to form protein-loaded nanogel (NGCA-CC). By adjusting the ratio of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 44 publications
2
35
0
2
Order By: Relevance
“…After accumulating into the acidic tumor tissue through the enhanced permeation and retention (EPR) effect, the amide bond slowly cleaves and thus exposes the positive charge, which eventually promotes cell internalization. Therefore, maleamic acids and their derivatives, by virtue of their unique weak acid sensitivity and charge conversion have been widely used as smart carriers to deliver nucleic acids (Meyer et al, 2009), proteins (Zhang et al, 2015;Lee et al, 2007) and drugs (Du et al, 2011;Chen et al, 2015;Han et al, 2015). Simple methods to control the ratio of two positional isomers of mono-substituted maleamic acids and a highly efficient way to synthesize di-substituted maleamic acids have been reported (Su et al, 2017).…”
Section: Chemical Contextmentioning
confidence: 99%
“…After accumulating into the acidic tumor tissue through the enhanced permeation and retention (EPR) effect, the amide bond slowly cleaves and thus exposes the positive charge, which eventually promotes cell internalization. Therefore, maleamic acids and their derivatives, by virtue of their unique weak acid sensitivity and charge conversion have been widely used as smart carriers to deliver nucleic acids (Meyer et al, 2009), proteins (Zhang et al, 2015;Lee et al, 2007) and drugs (Du et al, 2011;Chen et al, 2015;Han et al, 2015). Simple methods to control the ratio of two positional isomers of mono-substituted maleamic acids and a highly efficient way to synthesize di-substituted maleamic acids have been reported (Su et al, 2017).…”
Section: Chemical Contextmentioning
confidence: 99%
“…145,161 Surface-charge switching has therefore received interest as a drug delivery mechanism. 28,[209][210][211] Charge conversion of anionic nanoparticles into cationic nanoparticles, greatly enhances their cellular uptake. 145 Du et al reported a PEGdiacrylate-crosslinked 2-aminoethyl methacrylate nanogel, of which the primary amine groups were functionalized with 2,3-dimethylmaleic anhydride.…”
Section: Charge Conversionmentioning
confidence: 99%
“…74,87,148,310,311 Moreover, the responsive properties of nanogels offer possibilities for triggered release by incorporating enzymatically degradable, 225 bioreducible, 129,312 and pH-labile bonds. 73,74,211,310 Figure 20: Microgel-encapsulated 2-(diethylamino)ethyl methacrylate-co-tert-butyl methacrylate nanogels for oral siRNA-delivery: after degradation of the microgel matrix, fluorescently labeled nanogels were added to murine macrophages, showing cellular uptake (A, cell nuclei are stained in blue, the cell wall in red and the nanogels in green). Delivery of TNF-α knockdown siRNA showed no significant difference between the nanogels and Lipofectamine (B).…”
Section: Protein Deliverymentioning
confidence: 99%
See 2 more Smart Citations